Prostate specific antigen molecular forms in breast cyst fluid and serum of women with fibrocystic breast disease - Borchert, Gudrun H. (J Clin Lab Anal, 1999)
We have analyzed matched serum and breast cyst fluid samples for total PSA from 148 patients with fibrocystic breast disease. We have also determined the molecular forms of PSA (free PSA and PSA bound to α(1)‐antichymotrypsin) in 78 breast cyst fluid samples. We found that total PSA can be detected in all cyst fluids and in about 75% of female sera. The median total PSA concentration in breast cyst fluid (bcf) is about 30 times higher than the median in the corresponding sera. Breast cyst fluid and serum PSA are not correlated with each other. Total serum PSA is inversely associated with patient age but the inverse association between bcf PSA and age is weak. Lower total PSA in bcf was seen in women who breast feed, and higher bcf PSA is associated with multiple cysts. Type I cysts (with a high K(+)/Na(+) ratio) tend to have higher total PSA than Type II cysts. All but three of the fractionated cyst fluids (75/78; 96%) had free PSA as the predominant molecular form. The most consistent finding of our study was the positive association between the cyst fluid K(+)/Na(+) ratio and the free to bound PSA ratio. This association was confirmed by Spearman correlation as well as by Wilcoxon and chi‐square analysis. Secretory/apocrine cysts (Type I) tend to have more total PSA and proportionally more free PSA than transudative/flattened cysts (Type II). J. Clin. Lab. Anal. 13:75–81, 1999. © 1999 Wiley‐Liss, Inc.